Use of a Picosecond Alexandrite Laser for Treating Acquired Bilateral Nevus of Ota‐Like Macules in Chinese Patients. Issue 10 (13th April 2020) - Ding, Hui; Yang, Yin; Guo, Lifang; Lin, Tong
Abstract : Background and Objectives: Acquired bilateral nevus of Ota‐like macules (ABNOM) is common among the Chinese population. There have been few studies on the use of a picosecond alexandrite laser for the treatment of ABNOMs. The goal of this study was to evaluate the efficacy and safety of a 755 nm picosecond alexandrite laser for the treatment of ABNOMs. Study Design/Materials and Methods: A total of 225 subjects diagnosed with ABNOMs were included in this retrospective study. A 755 nm picosecond alexandrite laser system was used to treat all subjects. The safety and effectiveness of the laser were determined using a clinical photo assessment. The correlating factors of the patients, including the age, Fitzpatrick skin type, lesion location, lesion color, treatment procedures, melasma, and outcomes, were analyzed. Results: The patients underwent one to four treatment sessions with clinical clearance (>90%) rates of 8.89%, 30.99%, 56.65%, and 60.00%, respectively. A higher number of sessions was positively associated with a better treatment response. The hyperpigmentation incidence rate was 22.67%, and one case of hypopigmentation was observed. Conclusion: Our results suggest that a picosecond alexandrite laser is an effective and safe approach for treating ABNOMs in Chinese patients. Lasers Surg. Med. © 2020 Wiley Periodicals, Inc.